Separation of carvone by batch distillation from the mixture obtained from limonene oxidation (2022)
ABSTRACT : Limonene is the main constituent of citrus oils whose oxidation produces a set of fine chemical compounds such as carvone, carveol, and limonene 1,2-epoxide. This contribution reports the results of the experimental evaluation and computational simulation of carvone separation by fractional distillation from the reaction mixture. Carvone was obtained from limonene oxidation over a perchlorinated iron phthalocyanine supported on modified silica catalyst (FePcCl16 − NH2 − SiO2) and t-butyl hydroperoxide (TBHP) as oxidant. Both experimental and simulation results support that fractional distillation (in batch and continuous) is a suitable technique for concentrating carvone. However, in the presence of water, the formation of immiscible L-L phases makes the experimental separation of carvone more difficult. Simulation results of the batch distillation incorporating the NRTL-RK thermodynamic model indicate that if water, acetone, and t-butanol are previously removed from the reaction mixture, carvone composition can be enriched in the reboiler from 4% up to 50%, or around 86.5% if the removal is in a third distillate cut under vacuum conditions.